Aristotelic Intertextuality between "A Esmorga" and "Bodas de sangre" in the Representation of the Spanish Fatum Malus - Stratan, Sebastian (Madrygal. Revista de Estudios Gallegos, 2013)
This paper intends to outline the similarities and differences between Eduardo Blanco Amor’s A Esmorga and Federico García Lorca’s opus magnum, Bodas de sangre. The perspective we employ in this study is the analysis of the manner in which the two authors use the eternal Aristotelic precepts in the creation of now models of tragedy. That is, the manipulation of the Aristotelic paradigm formulated in his Poetics. To this end, we also focus on the fertile literary relationship between Blanco Amor and Lorca which, according to various studies related to this topic, mirrors itself in the two texts that constitute the object of this analysis.